2017
DOI: 10.1371/journal.pone.0171687
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of severe pneumonia in Ecuadorian children

Abstract: BackgroundIn Latin America, community-acquired pneumonia remains a major cause of morbidity and mortality among children. Few studies have examined the etiology of pneumonia in Ecuador.MethodsThis observational study was part of a randomized, double blind, placebo-controlled clinical trial conducted among children aged 2–59 months with severe pneumonia in Quito, Ecuador. Nasopharyngeal and blood samples were tested for bacterial and viral etiology by polymerase chain reaction. Risk factors for specific respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
46
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 84 publications
7
46
2
1
Order By: Relevance
“…This agrees with previous reports that also pointed to lower frequencies of ADV infection in nonsevere respiratory infections . However, human ADV 55 has been responsible for large outbreaks of severe cases of pneumonia in adult patients, with other studies having reported children with severe adenoviral pneumonia . The difference between these findings might be due to viral subtypes, given that some subtypes are significantly more pathogenic than others …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This agrees with previous reports that also pointed to lower frequencies of ADV infection in nonsevere respiratory infections . However, human ADV 55 has been responsible for large outbreaks of severe cases of pneumonia in adult patients, with other studies having reported children with severe adenoviral pneumonia . The difference between these findings might be due to viral subtypes, given that some subtypes are significantly more pathogenic than others …”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the majority of studies of children with severe CAP have reported RSV as the most common pathogen . For example, Jonnalagadda et al investigated viral etiology in 406 children with severe pneumonia and reported that RSV was the most common virus identified in 39% of subjects. In this context, the development of new vaccines and/or antivirals against RSV is crucial for prevention and treatment of RSV infections, especially in cases of CAP.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Ecuadorian children also found an association between being underweight and increased odds of RSV [33]. The detection of influenza virus among our study population is also found to be consistent with previous studies involving children with severe pneumonia [33,34]. It is important to note that in developed countries respiratory viruses were detected in up to 81% of young children with pneumonia, with RSVbeing the most frequently detected virus in most studies, ranging from 7% to 48% [35][36][37].…”
Section: Discussionsupporting
confidence: 92%
“…The only other study on viral etiology of pneumonia in malnourished children was conducted in Gambia in 1994 and detected 35% viral etiology in malnourished children with pneumonia and 25% in children Viral etiology of pneumonia among severely malnourished children without pneumonia, which is much lower than what we have found in our investigation [27]. A recent study in Ecuadorian children also found an association between being underweight and increased odds of RSV [33]. The detection of influenza virus among our study population is also found to be consistent with previous studies involving children with severe pneumonia [33,34].…”
Section: Discussioncontrasting
confidence: 86%
“…[21][22][23] Studies conducted in Latin America report frequencies ranging from 0.74% to 43.8%. [24][25][26] Most of the reports are from a previously healthy pediatric population.…”
Section: Discussionmentioning
confidence: 99%